Comparative Changes in the Quality of Pickles Prepared from Pacific White Shrimps (Litopenaeus vannamei) grown in Inland Saline Water and in Brackish Water during Storage - D. M. Affarin Tinku; Binaya Bhusan Nayak; K. A. Martin Xavier; V. Hari Krishna; Gopal Krishna; Amjad Khansaheb Balange (Fishery Technology, 2022)
Rearing of Pacific white shrimp (Litopenaeus vannamei) in inland saline water, the non- natural environment and compromised or stressed condition, may affect the meat quality and flavour of the shrimp. In this study, an attempt has been made to develop shrimp pickles from inland saline water reared vannamei (ISRV) and compare its quality with that from brackish water reared vannamei (BWRV) at room temperature for 5 months. The pickles prepared from ISRV had tantamount protein (31.05% w/w), high fat (10.23% w/w) and low ash (6.79% w/w) content as compared with BWRV pickles, which had protein, fat and ash content as 29.55%, 9.32% and 7.74% respectively. No significant difference was observed in the sensory scores of the pickles. Trimethylamine, total volatile base nitrogen and total viable bacterial count were significantly increasing during storage, however, remained within the acceptable limits. The lipid oxidation and hydrolysis parameters like peroxide value and free fatty acid content increased during storage. It could be concluded that overall quality and shelf life of shrimp pickles prepared from ISRV was comparable with BWRV and there was no significant effect observed under storage conditions.